Innovative Alternative Zinc Supplementation for Stunted Children from Pumpkin Seeds in the Form of Gummy Candy - Chitra Astari; Al Syahril Samsi; Waode Suiyarti; Sunarto S; Asmila (Postgraduate, University of Mataram, 2025)
Stunting is a chronic nutritional problem that is a big challenge in Indonesia, with a prevalence of 30.8% in 2018. The main cause of stunting is zinc deficiency, affecting the growth and development of children. Yellow pumpkin seeds are known to be rich in zinc content and can be used as an alternative source of zinc to prevent stunting in children. The purpose of the study is to make an innovation of Gummy Candy zinc yellow pumpkin seeds as an alternative to supplementation in Stunting, To test the evaluation of the physical and safe characteristics of Gummy Candy zinc zinc pumpkin seeds as an alternative to supplementation in stunted children. The research method uses an experimental with a quantitative approach. The results of the evaluation test of the physical characteristics of Gummy Candy preparations were obtained that the preparation has good characteristics seen from the attractive shape, chewy texture, slightly sour and sweet taste. The weight uniformity test did not deviate from the test and the pH test 4 was met for the pH of the Gummy Candy preparation which was 4-5. The zinc level test in the Gummy Candy made showed the presence of zinc contained in the preparation. Conclusion Gummy Candy zinc yellow pumpkin seeds as an alternative to supplementation in stunted children using 2 bases, namely gelatin and carrageenan printed with the shape of a heart, producing a preparation product that can attract children's attention, Giving processed products of yellow pumpkin seeds can increase the status of zinc in children at risk of stunting.